Mathematical modeling and experimental study of a two-stage fixed-bed heat storage system for heat recovery of flue gases. (October 2020) - Rahimi, A.; Farrokhi, M.; Hatamipour, M.S.; Moradi, M.
Highlights: Experimentation & mathematical modeling of energy recovery from the flue gases. Paraffin encapsulation within PE spheres as storage material at low temperatures. Thermal energy recovery from the flue gases in a packed bed using PCM. Performance assessment of a packed bed thermal energy storage and recovery system. Abstract: This paper presents the results of experimental study and mathematical modeling of thermal energy recovery from the flue gases in a packed bed using phase change materials (PCMs). Air and water were used as the heat transfer fluids (HTFs) in the heating and cooling periods, respectively. Paraffin wax was used as the PCM which was encapsulated within polyethylene spheres of 40 mm diameter. The effect of temperature and velocity of the entering air to the bed on the system performance was investigated. In addition, mathematical modeling was conducted, and its numerical results were compared with experimental data. Moreover, two dimensionless parameters (i.e. efficiency and yield) were defined to evaluate the system performance under various operating conditions. The results of this study showed that the efficiency of energy recovery in the considered system could be increased by increasing the inlet gas temperature and decreasing the inlet gas velocity. A 40% increase in inlet gas temperature at constant gas velocity increases the system efficiency by up to 44%. Besides, the mathematical modeling results showed a good agreement with the experimental data.